“Turun” as Participatory Budgeting Practices based on Siri' Na Pesse at the Death Ceremony in Baebunta, North Luwu Regency, Indonesia - Tenrigau, Andi Mattingaragau; Dahlan, Herawati; Aida, Nur (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This study aims to determine participatory budgets of siri’ na pesse in “turun” tradition of death events in Baebunta, Luwu Utara Regency. The study uses an interpretive paradigm with a methodological and ethnographic study of siri’ na pesse. The results show that